The New American Zombie Gothic: Road Trips, Globalisation, and the War on Terror. Issue 2 (1st November 2015) - Unknown
Abstract : American zombie Gothic films have changed markedly in their tone, style, and structure since September 11, an evolution that expands the Gothic mode to include the mobility of the narratives' protagonists, a popularisation of the movies, and an increased engagement with a multi-ethnic, international community. To remain timely, relevant, and commercially viable, such alterations must occur, and these shifts in particular can best be explained by the changing cinematic marketplace, the influence of videogames, and the policies and anxieties resulting from the (inter)national trauma of 9/11 and the War on Terror. This essay examines the film version of World War Z as a key text for exploring the current transition from a localised siege narrative to an international kind of 'road trip' movie, a shift largely tied to the popularity of zombie-themed videogames.